The Relations between Male and Female Participants in Using Assertive Speech Acts for Interactions in The Ellen DeGeneres Show - Maharani, Suri; Mujiyanto, Januarius; Warsono, Warsono (Universitas Negeri Semarang, 2020)
As an act of communication, people tend to speak with what comes to their minds and beliefs which are called assertive or representative speech acts concerning what the speaker believes to be the case or not. In this regard, this study aimed to explain the realization of assertive speech acts of male and female interactions in The Ellen DeGeneres Show and the relationship between male and female participants in realizing the assertive speech acts in terms of power, social distance, and rank of imposition. To expound this research more detail, a qualitative method was applied through direct observation of the videos and transcripts downloaded. Those data were supported by the theory of Searle and Vanderveken (1985) and Brown and Levinson (1987). From the data collected, there were 22 out of 32 types of assertive speech acts employed by male and female participants. There were no disclaim, notify, retrodict, insist, hypothesize, swear, testify, admit, accuse, and blame in their interactions. Mostly, males used affirm, inform, and state during their shows representing that they acted to exert dominance and achieve obvious outcomes. Whereas, female ones used state, affirm, and followed by inform acts to deliver their thoughts indicating that they used communication as a tool to enhance social connection and create relationships. It is in line that men are goal-oriented, while women are relationship-oriented. Moreover, adult participants had the same level in the matter of power and social distance which affected how they interacted through more multifarious assertive speech acts than the young ones. Besides, there were a few impositions between male and female as the topic given had already talked before, hence the possibility of threatening the speaker’s face is not very highly occurred. Based on this study, hopefully, people will know how to make words fit the world appropriately.